Chemotype differentiation and environmental drivers of bioactive metabolites in Cordyceps chanhua from diverse geographical origins - Qiucheng Luo; Gangxiang Fei; Xiaoguang Tian; Shuang Han; Jingqiang Guan; Bo Song; Longzhan Gan; Yeming Zhou; Zhijie Wang; Hongbo Lan; Xiao Zou (Biochemical Systematics and Ecology, 2026)

First record of Fraxinoxylon (Oleaceae) from the Miocene of Sihong, Jiangsu Province, China, and its palaeogeographic implication - Yanbin Zhu; Ya Li; Xiaohua Zhou; Yanfeng Song; Kai Liu; Ren Jiang; Yeming Cheng (Review of Palaeobotany and Palynology, 2026)

Divergent Responses to 16 Years Near-Natural Transformation: Forest-Type Specific Regulation of Soil Microbial Communities in Subtropical Coniferous Plantations - Angang Ming; Jian Chen; Weiei Shu; Xiaoguo Zhou; Yuying Liang; Huilin Min; Guangyu Xue; Dongjing Sun; Yi Tao; Yeming You; Yingzhuo Xi; Shirong Liu (Journal of Soil Science and Plant Nutrition, 2026)

Investigation of the hydrodynamic characteristics of the underwater propulsion pump blade based on a bionic strategy - Miao Jin; Haoran Liu; Guoyong Jin; Fangming Zhou; Yeming Lu; Xiaofang Wang (Ocean Engineering, 2025)

Mild heating modification of disulfide bond-linked protein aggregates and the green process for the preparation of soybean globulins - Longzheng Zhou; Xiaoxiao Feng; Xingfei Li; Xiangzhen Kong; Yeming Chen; Caimeng Zhang; Yufei Hua (Food Research International, 2025)

Maotai Town's peculiarity creates unmatched sauce-flavor liquor - A review - Shuang Han; Youcui Yang; Yeming Zhou; Qing He; Mingqian Liu; Xiao Zou (Food and Humanity, 2025)

Endophytic colonization via Cordyceps cateniannulata induces a growth-enhancing effect and increases the resistance of tomato plants against Tetranychus urticae (Koch) - Jingqiang Guan; Jing Liu; Jianyu Gou; Zhongshun Xu; Yeming Zhou; Xiao Zou (Crop Protection, 2025)

Establishment of Agrobacterium tumefaciens-mediated genetic transformation of the entomopathogenic fungus Hirsutella satumaensis - Yongli Feng; Jiaojiao Qu; Xiao Zou; Wei Cao; Yeming Zhou (Fungal Biology, 2025)

Structured neural networks for CPUE standardization: A case study of the blue endeavour prawn in Australia's Northern Prawn Fishery - Yeming Lei; Shijie Zhou; Nan Ye (Fisheries Research, 2024)

Spatial pattern, source apportionment, and source-oriented health risk quantifying of heavy metals in farmland soils of southern China - Bifeng Hu; Xiangyu He; Jiumao Zhou; Hong Zhang; Yeming Dai; Zhige Wang; Yefeng Jiang; Yangzhu Zhang; Pengbo Zhang; Zhou Shi (Environmental Monitoring and Assessment, 2024)

Spatial-temporal neural networks for catch rate standardization and fish distribution modeling - Yeming Lei; Shijie Zhou; Nan Ye (Fisheries Research, 2024)

Effectiveness and safety of Sanhan Huashi granules versus nirmatrelvir–ritonavir in adult patients with COVID-19: A randomized, open-label, multicenter trial - Xiaohui Zou; Kang Chang; Guohui Fan; Huanwei Zheng; Hezheng Shen; Liang Tang; Yingying Yang; Yeming Wang; Linhua Zhao; Hong Lv; Xin Zhou; Xiaoming Shen; et al. (Science Bulletin, 2024)

Characterization of mung bean endogenous proteases and globulins and their effects on the production of mung bean protein - Qianqian Zhou; Lili Wang; Yaowen Zhang; Caimeng Zhang; Xiangzhen Kong; Yufei Hua; Yeming Chen (Food Chemistry, 2024)

Stability Analysis and Deformation Control of Tunnel with Extremely Weak Surrounding Rocks Caused by Strike-Slip Fault Activity - Ziquan Chen; Qixiang Yan; Zihan Zhou; Chuan He; Tiansheng Li; Yeming Bao (Rock Mechanics and Rock Engineering, 2023)

Underwater propeller turbine blade redesign based on developed inverse design method for energy performance improvement and cavitation suppression - Yeming Lu; Zhenyang Guo; Zeyu Zheng; Wei Wang; Hui Wang; Fangming Zhou; Xiaofang Wang (Ocean Engineering, 2023)

Cerebral ischemic injury after transcatheter aortic valve replacement in patients with pure aortic regurgitation - Xianbao Liu; Hanyi Dai; Jiaqi Fan; Dao Zhou; Gangjie Zhu; Abuduwufuer Yidilisi; Jun Chen; Yeming Xu; Lihan Wang; Jian’an Wang (Journal of Zhejiang University-SCIENCE B, 2023)

Comparison of aroma active compounds in cold- and hot-pressed walnut oil by comprehensive two-dimensional gas chromatography-olfactory-mass spectrometry and headspace-gas chromatography-ion mobility spectrometry - Ying Xu; Shuang Bi; Xiaoyuan Niu; Yeming Chen; Ye Liu; Qi Zhou (Food Research International, 2023)

Evaluating methods for estimating shark natural mortality rate and management reference points using life‐history parameters - Shijie Zhou; Roy A. Deng; Matthew R. Dunn; Simon D. Hoyle; Yeming Lei; Ashley J. Williams (Fish and Fisheries, 2022)
Sharks (class Chondrichthyes, subclass Elasmobranchii) typically have a long lifespan, slow growth rate and low fecundity, leading to low productivity and hence relatively high vulnerability to fishing. Information for managing fisheries catches of elasmobranchs is often lacking, because elasmobranchs are usually non‐target species, often with low abundance. It is more feasible to develop management reference points for elasmobranchs based on their life‐history information than through traditional stock assessments. The natural mortality rate ( M ) is the leading life‐history parameter (LHP) required by many methods for developing reference points and is itself often derived indirectly from other LHPs. In this paper, we evaluate nine M estimators, using 15 shark stocks in the Western and Central Pacific Ocean as examples. We then compare four methods for developing fishing mortality reference points F msy , including empirical modelling, the Euler‐Lotka equation, an M ‐productivity‐based method and the spawning potential rate converted method. Our analyses show that popular M estimators developed mainly from teleost data resulted in large deviations from the average and were not suitable for elasmobranchs. All four methods for estimating F msy performed similarly. However, the empirical method is very simple and cost‐effective and tended to produce smaller deviations from the average than the other three methods. Nonetheless, it is recommended that multiple methods should be used to minimize possible bias and reflect uncertainty, if the required LHPs are available.

Identifying spawner biomass per‐recruit reference points from life‐history parameters - Shijie Zhou; André E. Punt; Yeming Lei; Roy Aijun Deng; Simon D. Hoyle (Fish and Fisheries, 2020)
Analysis of spawning biomass per‐recruit has been widely adopted in fisheries management. Fishing mortality expressed as spawning potential ratio (SPR) often requires a reference point as an appropriate proxy for the fishing mortality that supports a maximum sustainable yield— F MSY . To date, a single generic level between F 30% and F 40% is routinely used. Using records from stock assessments in the RAM Legacy Database (RAMLD), we confirm that SPR at MSY (SPR MSY ) is a declining function of stock productivity quantified by F MSY . We then use general linear models (GLM) and Bayesian errors‐in‐variables models (BEIVM) to show that SPR MSY can be predicted from life‐history parameters (LHPs, including maximum lifespan, age‐ and length‐at‐maturation, growth parameters, natural mortality, and taxonomic Class ) as well as gear selectivity. The calculated SPR MSY ranges from about 13% to 95% with a mean of 47%. About 64% of the stocks in the RAMLD require SPR MSY > 40%. Modelling SPR MSY reveals that LHPs plus Class explain 61% of the deviance in SPR MSY . Faster‐growing, low‐survival, and short‐lived species generally require a high SPR. With equal LHPs, elasmobranchs require about 20% higher SPR MSY than teleosts. When F MSY is estimated from fisheries that harvest older fish, increasing the vulnerable age by one year leads to about an 8% increase in SPR MSY . The BEIVM yields smaller variance and bias than the GLM. The models developed in this study could be used to predict SPR MSY reference points for new stocks using the same LHPs for calculating F x% , but without knowledge of the stock‐recruitment parameters.

Optimal rotation length for carbon sequestration in Eucalyptus plantations in subtropical China - Xiaoguo Zhou; Yuanguang Wen; Uromi Manage Goodale; Hua Zuo; Hongguang Zhu; Xiaoqiong Li; Yeming You; Li Yan; Yong Su; Xueman Huang (New Forests, 2017)

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.